MODEL PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN MELALUI KEPUASAN PELANGGAN DI STARBUCKS BALE KOTA TANGERANG - Amalia, Lia; Fellicia, Jovita (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
This study aims to determine the effect of product and service quality influence on customer loyalty through customer satisfaction as an intervening variable at Starbucks Bale Kota Tangerang. Independent variables consist of product quality and service quality, the dependent variable consists of customer loyalty and variables which include customer satisfaction. This research was conducted at Starbucks Bale Kota which is engaged in sales, located in Tangerang. The background behind sales research at Starbucks Bale Kota is indeed growing, but most of the sales come from new customers, not old customers or repurchases and in this study aims to see what influences the sense of customer loyalty to Starbucks Bale Kota. The authors of this study take product quality and service quality variables because these variables are in a dominant position in the Starbucks Bale Kota phenomenon. The sample used was 170 respondents with a sampling technique that is purposive sampling. The method of analysis used in this study is a non-probability sampling method with a research technique in the form of Path Analysis. The results showed that product quality and service quality had a positive and significant effect on customer satisfaction and customer loyalty. And customer satisfaction as an intervening variable is proven to have a greater influence than the direct effect.Keywords: product quality, service quality, customer satisfaction, customer loyalty